1997
DOI: 10.1037/0021-9010.82.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of GATB scores for immigrants and majority group members: Some Dutch findings.

Abstract: The central question addressed in this article is whether the test scores of immigrants and majority group members reflect the same dimensions. Use was made of scores on the Dutch version of the General Aptitude Test Battery on first-generation immigrants (N = 1,322) and majority group members (N = 806) who applied for blue-collar jobs in the Netherlands. The group differences with respect to the construct validity were small. Spearman's hypothesis that general intelligence is the predominant factor determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…Support for Spearman's hypothesis was found in samples of adults (te Nijenhuis & van der Flier, 1997, secondary school children (te Nijenhuis, Evers, & Mur, 2000) and young children (te Nijenhuis, Tolboom, Resing, & Bleichrodt, 2004). In South Africa comparisons were made of Blacks, Whites, and Indians (Lynn & Owen, 1994).…”
Section: Spearman's Hypothesismentioning
confidence: 70%
“…Support for Spearman's hypothesis was found in samples of adults (te Nijenhuis & van der Flier, 1997, secondary school children (te Nijenhuis, Evers, & Mur, 2000) and young children (te Nijenhuis, Tolboom, Resing, & Bleichrodt, 2004). In South Africa comparisons were made of Blacks, Whites, and Indians (Lynn & Owen, 1994).…”
Section: Spearman's Hypothesismentioning
confidence: 70%
“…This method has been widely adopted as a method for investigating factors associated with the g-factor, and it has been applied to test if the Spearman hypothesis can account for performance differences between other groups, such as non-immigrant and immigrant groups. Using the method of correlated vectors te Nijenhuis & van der Flier (1997, 2003 concluded that performance differences between immigrants and non-immigrants in the Netherlands can be explained by the Spearman hypothesis in combination with language bias in tests with a strong verbal component.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…A mean (Spearman's rho) correlation of .59 (sd .12), obtained using this procedure, has been reported on the basis of 11 studies (Jensen, 1985). For other applications of Jensen's test, see Naglieri and Jensen (1987), Lynn and Owen (1994), te Nijenhuis and van der Flier (1997), and Rushton (1999).…”
Section: Introductionmentioning
confidence: 99%